A method for preparing a lightweight ceramicizable titanium-modified phenolic-based composite material

By introducing titanate in phenolic resin to form a TI-O key to form a three-dimensional network structure of carbon-titanium mute, the existing fiber enhanced phenolin gas gel composite material is oxidized and radiated heat dissipation at high temperature. The preparation of lightweight can be mitigated phenolic composite materials, which has excellent thermal stability and antioxidant properties.

CN118580541BActive Publication Date: 2025-01-28HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410787954.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-01-28
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

现有纤维增强酚醛气凝胶复合材料在使用过程中存在氧化和/或辐射散热的问题,难以满足未来飞行器的热环境需求。

Method used

The preparation method of a lightweight titanium titanium titanium modified phenolic base composite material is used. By mixing the phenolic resin with titanate, the Ti-O key is formed, and the main chain of the phenolic C main chain is connected to form carbon-titanium-titanium wearing and mutual wear. The three -dimensional stereo network structure improves the chemical stability and thermal stability of the material, and achieves in -situ ceramics at high temperature.

Benefits of technology

It improves the chemical stability and thermal stability of the phenolic resin, and achieves ceramicization at high temperature. It has excellent antioxidant performance and low thermal conductivity, and is suitable for a wider temperature range and complex heat environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580541B_ABST
    Figure CN118580541B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a lightweight, ceramicizable titanium-modified phenolic-based composite material. The method comprises the following steps: preparing a phenolic solution; preparing a titanium-containing solution; adding the titanium-containing solution to the phenolic solution within 10 seconds and stirring at a speed of 200 to 400 r / min at room temperature to obtain a titanium-modified phenolic resin, wherein the stirring time is determined according to the titanate content in the titanium-containing solution; introducing the titanium-modified phenolic resin into a fiber preform, and then sequentially curing, solvent replacement and drying to obtain a lightweight, ceramicizable titanium-modified phenolic-based composite material. The titanium-modified phenolic matrix in the present invention improves the chemical stability and thermal stability of the composite material, and can realize in-situ surface ceramicization and reflect infrared thermal radiation at high temperatures, and is expected to replace the existing fiber-reinforced phenolic aerogel composite material to become a new type of aerospace thermal protection material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phenolic-formaldehyde-based composite materials, and in particular relates to a method for preparing a lightweight ceramicizable titanium-modified phenolic-formaldehyde-based composite material. Background Art

[0002] The vigorous development of the country's aerospace industry has spawned a large number of new thermal protection materials. Among them, phenolic resin aerogel with a porous structure has been used in many space missions as an efficient thermal protection material. Its uniform nanopore structure can effectively extend the heat transfer path, block gas convection and thus reduce thermal conductivity. It uses mass ejection and reverse injection mechanisms to shield a large amount of heat in severe aerodynamic thermal environments. It is a very potential aerospace thermal protection material. With the deepening of research, it has gradually been discovered that the disadvantages of traditional lightweight fiber-reinforced phenolic aerogel composite materials, such as easy decomposition in an oxidizing atmosphere and weak shape retention during the ablation process, are also gradually discovered. Therefore, it is urgent to modify the composite material appropriately to adapt to more complex thermal environments.

[0003] The main aspect of composite material modification is the modification of the phenolic resin matrix. Since radiative heat conduction accounts for a large proportion in high temperature environments and the matrix material provides the main heat insulation function, domestic and foreign researchers have focused on the heat protection and functionalization of lightweight aerogel matrices. The matrix modification methods are divided into organic hybridization and inorganic blending, among which boron-modified phenolic resin, silicon-modified phenolic resin and various inorganic filler modifications are the main ones. These modification methods can improve the thermal stability, ablation resistance, processability and chemical stability of phenolic resin to a certain extent, but still cannot meet the quality stability and / or reusability of use in an aerobic environment. Therefore, it is urgent to study an ablation-resistant and heat-stable titanium-modified phenolic resin to solve the oxidation and / or radiation heat dissipation problems of existing fiber-reinforced phenolic aerogel composites during use to meet the requirements of future aircraft.

[0004] In summary, it is very necessary to provide a method for preparing a lightweight and ceramicizable titanium-modified phenolic-based composite material. Summary of the invention

[0005] In order to solve one or more technical problems such as oxidation and / or radiation heat dissipation in the use of existing fiber-reinforced phenolic aerogel composite materials, the present invention provides a method for preparing a lightweight ceramic titanium-modified phenolic aerogel-based composite material. The density of the lightweight ceramic titanium-modified phenolic aerogel-based composite material prepared by the present invention is 0.30-0.53 g / cm 3 The titanium-modified phenolic matrix improves the chemical and thermal stability of the composite material, and can achieve in-situ surface ceramicization and reflect infrared thermal radiation at high temperatures. It is expected to replace the existing fiber-reinforced phenolic aerogel composite material and become a new type of aerospace thermal protection material.

[0006] In a first aspect, the present invention provides a method for preparing a lightweight ceramizable titanium-modified phenolic-based composite material, the method comprising the following steps:

[0007] (1) mixing a phenolic resin and a solvent and stirring the mixture at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a phenolic solution;

[0008] (2) mixing the curing agent and the solvent and stirring at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a mixed solution, and then adding titanate to the mixed solution and mixing evenly to obtain a titanium-containing solution;

[0009] (3) adding the phenolic solution to the titanium-containing solution within 10 seconds, and stirring at a speed of 200 to 400 r / min at room temperature to obtain a titanium-modified phenolic resin solution; in step (3), the stirring time is determined according to the titanate content in the titanium-containing solution;

[0010] (4) The fiber preform is impregnated with a titanium-modified phenolic resin solution, and then cured, solvent replaced and dried in sequence to obtain a lightweight, ceramicizable titanium-modified phenolic-based composite material.

[0011] Preferably, in the phenolic solution, the mass ratio of the phenolic resin to the solvent is (6-9):20; in the titanium-containing solution, the mass ratio of the curing agent, the titanate and the solvent is (0.5-2):(0.1-3):30; and / or in step (3), the mass ratio of the phenolic solution to the titanium-containing solution is 1:(0.8-1.2).

[0012] Preferably, in step (3), the stirring time decreases with the increase of the titanate content in the titanium-containing solution; preferably, when the mass ratio of the titanate to the solvent in the titanium-containing solution is greater than or equal to 0.1:30 and less than 1:30, the stirring time is 20 to 25 minutes; preferably, when the mass ratio of the titanate to the solvent in the titanium-containing solution is (1 to 2):30, the stirring time is 8 to 10 minutes; preferably, when the mass ratio of the titanate to the solvent in the titanium-containing solution is greater than 2:30 and less than or equal to 3:30, the stirring time is 8 to 10 seconds.

[0013] Preferably, in step (1), the phenolic resin is one or more of barium-modified phenolic resin, boron-modified phenolic resin, silicon-modified phenolic resin, zirconium-modified phenolic resin and epoxy-modified phenolic resin.

[0014] Preferably, in step (1) and / or step (2), the solvent is one or more of methylformamide, propylene glycol, ethylene glycol, dimethylaniline, and methylpyrrolidone; in step (2), the curing agent is one or more of paraformaldehyde, hexamethylenetetramine, aniline, formaldehyde, and melamine; and / or in step (2), the titanate is one or more of ethyl titanate, isopropyl titanate, and butyl titanate.

[0015] Preferably, in step (4), the curing is: first curing at 110-135°C for 2-4 hours, then curing at 140-165°C for 12-14 hours, and then curing at 170-195°C for 2-4 hours; using anhydrous ethanol for solvent replacement, the temperature of the solvent replacement is 50-70°C, the time for each solvent replacement is 18-30 hours, and the number of solvent replacements is 3-6 times; and / or the drying is vacuum drying at 170-190°C, preferably, the pressure of the vacuum drying is 1-10 kPa.

[0016] Preferably, the fiber used in the fiber preform is one or more of continuous carbon fiber, quartz fiber, glass fiber, and organic fiber; the structure of the fiber preform is a sutured structure, a needle-punched structure, a mesh structure, a 2.5D woven structure, or a three-dimensional woven structure. Preferably, the fiber preform is a three-dimensional needle-punched structure.

[0017] Preferably, the density of the fiber preform is 0.15-0.36 g / cm 3 , thickness is 10-30mm, single wire diameter is 6-7μm, needle density is 15-20 needles / cm 2 .

[0018] Preferably, the fiber preform is impregnated with the titanium-modified phenolic resin solution under a pressure of 1 to 10 kPa.

[0019] In a second aspect, the present invention provides a lightweight, ceramizable, titanium-modified phenolic-based composite material prepared by the preparation method described in the first aspect of the present invention.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects:

[0021] (1) The present invention grafts Ti-O bonds onto the C main chain of the traditional phenolic aerogel, which can effectively improve the chemical stability of the phenolic resin, and utilizes the alcoholysis of titanate to form Ti-O bonds and connect with the phenolic C main chain to form a three-dimensional network structure of carbon-titanium interpenetration. Since the bond energy of the Ti-O bond (662 kJ / mol) is higher than the CC bond energy (345.6 kJ / mol), the phenolic main chain can be partially strengthened after grafting, and the energy required for bond breaking is greater, thereby increasing the temperature for rapid pyrolysis of the phenolic resin, improving the high temperature stability and oxidation resistance of the phenolic aerogel, and being applicable to a wider temperature range. In addition, the fine pore structure and particle size of the titanium-modified phenolic resin in the present invention after being introduced into the fiber preform and cured also make the composite material have extremely low thermal conductivity, which plays a role in efficient heat insulation.

[0022] (2) Compared with the prior art, the ceramicizable titanium-modified phenolic-formaldehyde-based composite material prepared by the present invention can form a TiO2 ceramic functional phase in situ at high temperature, and use the ablation heat environment to achieve dense ceramicization of lightweight phenolic resin, avoiding the density increase and calcination process damage caused by the direct addition of ceramic phase; the introduced TiO2 ceramic functional phase is an excellent infrared sunshade, which can dissipate the radiant heat generated during the ablation process by the re-radiation effect, thereby obtaining a higher emissivity on the surface of the material. The new lightweight ceramicizable titanium-modified phenolic-formaldehyde-based composite material prepared by the present invention also has improved performance in terms of heat radiation resistance and reusability. The material can achieve the coupling effect of multiple heat protection mechanisms through regulation and design, providing ideas for the preparation of a new generation of thermal protection materials.

[0023] (3) The preparation method of the lightweight ceramic titanium-modified phenolic-formaldehyde-based composite material described in the present invention has the characteristics of simple process, simple raw materials, stable process, etc. In the preparation process of the present invention, it is necessary to adjust the stirring time of the titanium-modified phenolic resin according to the addition amount of titanate, so as to effectively control the structure and performance of the lightweight ceramic titanium-modified phenolic-formaldehyde-based composite material, so that the lightweight ceramic titanium-modified phenolic-formaldehyde-based composite material has extremely low thermal conductivity, plays a role of efficient heat insulation and has excellent antioxidant properties. The lightweight ceramic titanium-modified phenolic-formaldehyde-based composite material prepared by the present invention has a tightly bonded phase interface between the two phases, and the titanium-modified phenolic-formaldehyde aerogel matrix tightly wraps the reinforcing fiber, inheriting the excellent mechanical properties of the fiber. The lightweight ceramic titanium-modified phenolic-formaldehyde-based composite material prepared by the present invention has the characteristics of light weight, ablation resistance, low thermal conductivity, etc., and is expected to replace the existing fiber-reinforced phenolic-formaldehyde aerogel composite material to become a new type of aerospace thermal protection material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a preparation flow chart in some specific embodiments of the present invention;

[0025] Figure 2This is a macroscopic morphology of the lightweight, ceramicizable titanium-modified phenolic-based composite material obtained in Example 1 of the present invention;

[0026] Figure 3 It is the microstructure and element distribution energy spectrum of the lightweight ceramicizable titanium-modified phenolic-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In a first aspect, the present invention provides a method for preparing a lightweight ceramizable titanium-modified phenolic-based composite material, the method comprising the following steps:

[0029] (1) mixing a phenolic resin and a solvent and stirring the mixture at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a phenolic solution;

[0030] (2) mixing the curing agent and the solvent and stirring at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a mixed solution, and then adding titanate to the mixed solution and mixing evenly to obtain a titanium-containing solution; in the present invention, room temperature refers to room temperature of 15 to 30° C.;

[0031] (3) adding the phenolic solution to the titanium-containing solution within 10 seconds, and stirring at a speed of 200 to 400 r / min at room temperature to obtain a titanium-modified phenolic resin solution; in step (3), the stirring time is determined according to the titanate content in the titanium-containing solution; in step (3), preferably, the stirring time decreases with the increase of the titanate content in the titanium-containing solution. The present invention can ensure that the titanium-modified phenolic resin solution is not over-cured and has a suitable viscosity before impregnating the fiber preform through a reasonable stirring time; the present invention finds that titanate can be used as a cross-linking agent or catalyst to accelerate the curing reaction of phenolic resin. The higher the ester content, the faster the curing reaction rate will be, which is conducive to accelerating the uniform distribution of titanate. In addition, in order to avoid excessive gelation of the titanium-modified phenolic resin, the present invention controls the stirring time to decrease as the titanate content in the titanium-containing solution increases. Appropriate stirring time control can avoid side reactions caused by too fast titanate reaction, which is conducive to ensuring the quality and performance of the material. In the present invention, all of the phenolic solution is added to the titanium-containing solution within 10 seconds. The present invention finds that adding all of the phenolic solution in a short time can effectively control the reaction, which is conducive to more accurate control of the stirring time, thereby facilitating better product quality.

[0032] (4) The fiber preform is impregnated with a titanium-modified phenolic resin solution, and then cured, solvent-displaced (solvent replaced) and dried in sequence to obtain a lightweight, ceramicizable titanium-modified phenolic-based composite material (also referred to as a fiber-reinforced phenolic aerogel composite material); in the present invention, the impregnation is vacuum impregnation, and the pressure of the vacuum impregnation is, for example, 1 to 10 kPa. The present invention has no particular restriction on the amount of the titanium-modified phenolic resin solution, as long as the fiber preform can be completely immersed in the titanium-modified phenolic resin solution. The vacuum impregnation time is, for example, 5 to 30 minutes, and the vacuum impregnation temperature is, for example, room temperature 15 to 30°C.

[0033] The present invention grafts Ti-O bonds on the C main chain of the traditional phenolic aerogel, which can effectively improve the chemical stability of the phenolic resin, and utilizes the alcoholysis of titanate to form Ti-O bonds and connect with the phenolic C main chain to form a three-dimensional network structure of carbon-titanium interpenetration. Since the bond energy of the Ti-O bond (662 kJ / mol) is higher than the CC bond energy (345.6 kJ / mol), the phenolic main chain can be partially strengthened after grafting, and the energy required for its bond breaking is greater, which increases the temperature of the rapid pyrolysis of the phenolic resin, improves the high temperature stability and oxidation resistance of the phenolic aerogel, and is applicable to a wider temperature range. In addition, the fine pore structure and particle size of the titanium-modified phenolic resin in the present invention after being introduced into the fiber preform and cured also make the composite material have extremely low thermal conductivity, which plays a role in efficient heat insulation. Compared with the prior art, the ceramicizable titanium-modified phenolic-formaldehyde-based composite material prepared by the present invention can form a TiO2 ceramic functional phase in situ at high temperature, and use the ablation heat environment to achieve dense ceramicization of lightweight phenolic resin, avoiding the density increase and calcination process damage caused by the direct addition of ceramic phase; the introduced TiO2 ceramic functional phase is an excellent infrared sunshade, which can dissipate the radiant heat generated during the ablation process using the re-radiation effect to obtain a higher emissivity on the surface of the material. The new lightweight ceramicizable titanium-modified phenolic-formaldehyde-based composite material prepared by the present invention also has improved performance in terms of heat radiation resistance and reusability. The material can achieve a variety of heat protection mechanism coupling effects through regulation and design, providing ideas for the preparation of a new generation of thermal protection materials. The preparation method of the lightweight ceramicizable titanium-modified phenolic-formaldehyde-based composite material described in the present invention has the characteristics of simple process, simple raw materials, and stable process. During the preparation process of the present invention, it is necessary to regulate the stirring time of the titanium-modified phenolic resin according to the addition amount of the titanate, so that the structure and performance of the lightweight ceramic titanium-modified phenolic-based composite material can be effectively controlled, so that the lightweight ceramic titanium-modified phenolic-based composite material has extremely low thermal conductivity, plays a role of efficient heat insulation and has excellent antioxidant properties. The lightweight ceramic titanium-modified phenolic-based composite material prepared by the present invention has a tightly bonded phase interface between the two phases, and the titanium-modified phenolic aerogel matrix tightly wraps the reinforcing fiber, inheriting the excellent mechanical properties of the fiber. The lightweight ceramic titanium-modified phenolic-based composite material prepared by the present invention has the characteristics of light weight, ablation resistance, low thermal conductivity, etc., and is expected to replace the existing fiber-reinforced phenolic aerogel composite material to become a new type of aerospace thermal protection material.

[0034] Although there are related reports on titanium-modified phenolic resins in the prior art, what is different from the existing titanium-modified phenolic resins is that when obtaining the titanium-modified phenolic resin, the present invention quickly adds the phenolic solution to the titanium-containing solution and performs precise stirring time control, which can ensure that the titanium-modified phenolic resin and the fiber preform can have sufficient time to impregnate and react, and will not be over-cured before impregnation, and this rapid and precise reaction control helps to form a uniform microporous structure. The titanium-modified phenolic resin prepared by the present invention can ensure the uniform distribution of titanate in the phenolic resin. The uniformly distributed titanium-modified phenolic resin helps to form a uniform network structure during the curing process after being impregnated into the fiber preform, thereby helping the composite material to form a uniform porous structure and improve the porosity and pore structure uniformity; the titanate can react chemically with the phenolic resin during the curing process (molecular chains are cross-linked), and this process retains the porous structure of the phenolic aerogel, so that the cured aerogel has the characteristics of low density and low thermal conductivity, and the uniform titanium modification gives the composite material ceramic and antioxidant properties during the ablation process. Although CN 109160988B discloses a method for preparing a titanium-modified phenolic resin, the patent application discloses that a mixed solution A formed by titanate and acetylacetone is slowly added dropwise to an ethanol solution of phenolic resin under stirring at 15 to 30°C, and then stirred at 15 to 30°C for 0.1 to 1h to obtain the titanium-modified phenolic resin. However, the titanium-modified phenolic resin prepared by the patent only adopts a method to allow the titanate to exist stably in the phenolic resin, and does not have the ability to be prepared into fiber-reinforced aerogel later. This phenolic resin can only be used to make dense phenolic solids, such as paints, surface waterproof coatings, etc., and the pores of the titanium-modified phenolic resin prepared by the patent method are relatively large, and the large pores are not conducive to heat insulation, and cannot be used to prepare porous aerogel materials for heat insulation and ablation resistance.

[0035] According to some preferred embodiments, in the phenolic solution, the mass ratio of the phenolic resin to the solvent is (6-9):20 (for example, 6:20, 7:20, 8:20 or 9:20); in the titanium-containing solution, the mass ratio of the curing agent, the titanate and the solvent is (0.5-2):(0.1-3):30; and / or in step (3), the mass ratio of the phenolic solution to the titanium-containing solution is 1:(0.8-1.2).

[0036] According to some preferred embodiments, in step (3), the stirring time decreases as the titanate content in the titanium-containing solution increases; preferably, when the mass ratio of the titanate to the solvent in the titanium-containing solution is greater than or equal to 0.1:30 and less than 1:30, the stirring time is 20 to 25 minutes; preferably, when the mass ratio of the titanate to the solvent in the titanium-containing solution is (1 to 2):30, the stirring time is 8 to 10 minutes; preferably, when the mass ratio of the titanate to the solvent in the titanium-containing solution is greater than 2:30 and less than or equal to 3:30, the stirring time is 8 to 10 seconds.

[0037] In the present invention, preferably, by controlling the ratio of the components in the phenolic solution, the ratio of the components of the titanium-containing solution, the mass ratio of the phenolic solution to the titanium-containing solution, and controlling the stirring time of the phenolic solution and the titanium-containing solution according to the content of titanate in the titanium-containing solution, a titanium-modified phenolic resin solution with a suitable viscosity can be obtained. The present invention finds that appropriate viscosity helps the titanium-modified phenolic resin to adhere to the fiber surface, form a good interface bond, improve the overall performance of the composite material, ensure that the titanium-modified phenolic resin is uniformly impregnated into the fiber preform, and ultimately facilitate the preparation of a lightweight, ceramic titanium-modified phenolic-based composite material with high porosity and excellent performance (lightweight, ablation resistance, low thermal conductivity), that is, a fiber-reinforced phenolic aerogel composite material.

[0038] According to some preferred embodiments, in step (1): the phenolic resin is a commercial thermosetting phenolic resin, preferably, the phenolic resin is one or more of commercial barium-modified phenolic resin, boron-modified phenolic resin, silicon-modified phenolic resin, zirconium-modified phenolic resin, and epoxy-modified phenolic resin; the present invention has no particular limitation on the source of the barium-modified phenolic resin, boron-modified phenolic resin, silicon-modified phenolic resin, zirconium-modified phenolic resin, and epoxy-modified phenolic resin, and products that can be directly purchased on the market or products synthesized by existing methods can be used.

[0039] According to some preferred embodiments, in step (1) and / or step (2), the solvent is a high boiling point solvent, preferably, the solvent is one or more of methylformamide, propylene glycol, ethylene glycol, dimethylaniline, methylpyrrolidone; in step (2), the curing agent is one or more of paraformaldehyde, hexamethylenetetramine, aniline, formaldehyde, melamine; and / or in step (2), the titanate is one or more of ethyl titanate, isopropyl titanate, butyl titanate.

[0040] According to some preferred embodiments, in step (4): the curing is: first curing at 110-135°C for 2-4 hours, then curing at 140-165°C for 12-14 hours, and then curing at 170-195°C for 2-4 hours; using anhydrous ethanol for solvent replacement, the temperature of the solvent replacement is 50-70°C, the time for each solvent replacement is 18-30 hours, and the number of solvent replacements is 3-6 times; in the present invention, preferably, using anhydrous ethanol for solvent replacement at 50-70°C, which can reduce the time for solvent replacement and make it easier to fully perform solvent replacement; and / or the drying is vacuum drying at 170-190°C, preferably, the pressure of the vacuum drying is 1-10 kPa, and the time of the vacuum drying is 10-18 hours. According to some preferred embodiments, the fiber used in the fiber preform is one or more of continuous carbon fiber, quartz fiber, glass fiber, and organic fiber; the structure of the fiber preform is a sutured structure, a needle-punched structure, a mesh structure, a 2.5D woven structure, or a three-dimensional woven structure. Preferably, the fiber preform is a three-dimensional needle-punched structure.

[0041] According to some preferred embodiments, the density of the fiber preform is 0.15-0.36 g / cm 3 , thickness is 10-30mm, single wire diameter is 6-7μm, needle density is 15-20 needles / cm 2 ; In the present invention, the monofilament diameter refers to the monofilament diameter of the fiber used in the fiber preform; In the present invention, the laying method of the fiber preform can be any laying method; The preparation of the fiber preform is a conventional technology in the field.

[0042] According to some preferred embodiments, the fiber preform is impregnated with the titanium-modified phenolic resin solution at a pressure of 1 to 10 kPa (absolute pressure).

[0043] According to some specific embodiments, the preparation of the lightweight ceramizable titanium-modified phenolic-based composite material includes:

[0044] ① Preparation of phenolic solution: uniformly mix phenolic resin and solvent, stir at room temperature at a speed of 200-400 r / min for 1-3 hours to obtain a uniform and transparent phenolic solution;

[0045] ②Preparing a titanium-containing solution: Mix the curing agent and the solvent evenly, stir at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a uniform and transparent solution, add titanate to the solution and mix evenly to obtain a titanium-containing solution;

[0046] ③Preparing a titanium-modified phenolic resin solution: adding the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② within 10 seconds, and stirring at a speed of 200 to 400 r / min. The stirring time is determined according to the titanate content to obtain a titanium-modified phenolic resin solution;

[0047] ④ Impregnation, curing, solvent replacement and drying: the titanium-modified phenolic resin solution obtained in step ③ is introduced into (impregnated into) the fiber preform under a pressure of 1 to 10 kPa, the temperature is raised from room temperature to 110 to 135°C at a rate of 4 to 6°C / min for reaction for 2 to 4 hours, the temperature is further raised to 140 to 165°C for reaction for 12 to 14 hours, the temperature is further raised to 170 to 195°C for reaction for 2 to 4 hours, and then the mixture is cooled with the furnace to obtain a cured titanium-modified phenolic composite material semi-finished product; the obtained semi-finished product is immersed in anhydrous ethanol, the anhydrous ethanol is maintained at 60°C, the anhydrous ethanol is replaced every 24 hours, and the anhydrous ethanol is replaced 3 to 5 times, and vacuum dried at 170 to 190°C to obtain a thermally stable, lightweight, ceramicizable titanium-modified phenolic-based composite material.

[0048] In a second aspect, the present invention provides a lightweight, ceramizable, titanium-modified phenolic-based composite material prepared by the preparation method described in the first aspect of the present invention.

[0049] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.

[0050] Example 1

[0051] ① Preparation of phenolic solution: boron-modified phenolic resin (THC-800 produced by Shaanxi Taihang Fire Retardant Polymer Co., Ltd.) and ethylene glycol were mixed in a mass ratio of 7.5:20 and stirred at a speed of 300 r / min at room temperature of 25° C. for 1 hour to obtain a phenolic solution.

[0052] ②Preparing a titanium-containing solution: mixing hexamethylenetetramine and ethylene glycol and stirring at 300 r / min for 2 hours at room temperature of 25°C to obtain a uniform and transparent solution, adding butyl titanate to the solution and mixing evenly to obtain a titanium-containing solution; wherein the mass ratio of hexamethylenetetramine, butyl titanate and ethylene glycol is 1:2:30.

[0053] ③Preparing a titanium-modified phenolic resin solution: adding the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② within 10 seconds, and stirring at a speed of 300 r / min for 10 minutes to obtain a titanium-modified phenolic resin solution; wherein the mass ratio of the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② is 1:1.

[0054] ④Impregnation, curing, solvent replacement and drying: The titanium-modified phenolic resin solution obtained in step ③ was vacuum impregnated at a pressure of 10 kPa to obtain a volume density of 0.16 g / cm3 The carbon fiber preform is vacuum impregnated at room temperature 25°C and the vacuum impregnation time is 30min; after taking out the impregnated carbon fiber preform, the temperature is raised from room temperature 25°C to 120°C at a rate of 5°C / min for reaction for 3 hours, the temperature is continued to be raised to 155°C at a rate of 5°C / min for reaction for 12 hours, the temperature is continued to be raised to 180°C at a rate of 5°C / min for reaction for 3 hours, and then cooled to room temperature 25°C with the furnace to obtain a cured titanium-modified phenolic composite material semi-finished product; the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent replacement temperature is maintained at 60°C, the anhydrous ethanol is replaced every 24h, and replaced 4 times, and finally vacuum dried at 180°C (the vacuum drying pressure is 10kPa) for 12h to obtain a lightweight ceramicizable titanium-modified phenolic-based composite material.

[0055] The density of the lightweight ceramic titanium-modified phenolic-based composite material prepared in this embodiment is 0.43 g / cm 3 The thermal conductivity along the fiber thickness direction is 0.037W / (m·K), and the heat flux density is 3.6MW / m 2 The surface temperature of the sample exceeded 1900°C and the back surface temperature was only 73°C when it was exposed to the oxyacetylene flame for 30 seconds.

[0056] The macroscopic morphology of the lightweight ceramic titanium-modified phenolic-based composite material prepared in this embodiment is as follows: Figure 2 As shown in FIG. 1 , the microstructure and element distribution energy spectrum of the lightweight ceramicizable titanium-modified phenolic-based composite material prepared in this embodiment are as follows: Figure 3 shown.

[0057] Example 2

[0058] ① Preparation of phenolic solution: Mix silicon-modified phenolic resin and propylene glycol in a mass ratio of 8:20 and stir at a speed of 300 r / min for 2 hours at room temperature of 25° C. to obtain a phenolic solution.

[0059] ②Preparation of a titanium-containing solution: Mix paraformaldehyde and propylene glycol and stir at room temperature (25°C) at a speed of 300 r / min for 2 hours to obtain a uniform and transparent solution, add ethyl titanate to the solution and mix evenly to obtain a titanium-containing solution; wherein the mass ratio of paraformaldehyde, ethyl titanate and propylene glycol is 1.3:0.5:30.

[0060] ③Preparing a titanium-modified phenolic resin solution: adding the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② within 10 seconds, and stirring at a speed of 400 r / min for 25 minutes to obtain a titanium-modified phenolic resin solution; wherein the mass ratio of the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② is 1:1.

[0061] ④Impregnation, curing, solvent replacement and drying: The titanium-modified phenolic resin solution obtained in step ③ was vacuum impregnated at a pressure of 5 kPa to obtain a volume density of 0.23 g / cm 3 The quartz fiber preform is taken out, the vacuum impregnation temperature is room temperature 25°C, and the vacuum impregnation time is 30min; after taking out the impregnated quartz fiber preform, the temperature is raised from room temperature 25°C to 125°C at a rate of 6°C / min for reaction for 4 hours, the temperature is continued to be raised to 150°C at a rate of 6°C / min for reaction for 13 hours, the temperature is continued to be raised to 185°C at a rate of 6°C / min for reaction for 2 hours, and then cooled to room temperature 25°C with the furnace to obtain a cured titanium-modified phenolic composite material semi-finished product; the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent replacement temperature is maintained at 60°C, the anhydrous ethanol is replaced every 24h, and it is replaced 3 times, and finally vacuum dried at 175°C (the vacuum drying pressure is 10kPa) for 12h to obtain a lightweight ceramicizable titanium-modified phenolic-based composite material.

[0062] The density of the lightweight ceramic titanium-modified phenolic-based composite material prepared in this example is 0.42 g / cm 3 The thermal conductivity along the fiber thickness direction is 0.044W / (m·K), and the heat flux density is 3.6MW / m 2 The surface temperature of the sample exceeded 1900°C and the back surface temperature was only 87°C when it was exposed to the oxyacetylene flame for 30 seconds.

[0063] Example 3

[0064] ① Preparation of phenolic solution: barium-modified phenolic resin (B30 produced by Shaanxi Taihang Fire Retardant Polymer Co., Ltd.) and methylformamide (N-methylformamide) were mixed in a mass ratio of 7.5:20 and stirred at 350 r / min for 2 hours at room temperature of 25°C to obtain a phenolic solution.

[0065] ②Preparing a titanium-containing solution: Mix melamine and methylformamide and stir at 300 r / min for 2 hours at room temperature (25°C) to obtain a uniform and transparent solution, add isopropyl titanate to the solution and mix evenly to obtain a titanium-containing solution; wherein the mass ratio of melamine, isopropyl titanate and methylformamide is 1.5:2.5:30.

[0066] ③Preparing a titanium-modified phenolic resin solution: adding the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② within 10 seconds, and stirring at a speed of 400 r / min for 9 seconds to obtain a titanium-modified phenolic resin solution; wherein the mass ratio of the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② is 1:1.

[0067] ④Impregnation, curing, solvent replacement and drying: The titanium-modified phenolic resin solution obtained in step ③ was vacuum impregnated at a pressure of 4 kPa to obtain a volume density of 0.35 g / cm 3 The quartz fiber preform is taken out, the vacuum impregnation temperature is room temperature 25°C, and the vacuum impregnation time is 30min; after taking out the impregnated quartz fiber preform, the temperature is raised from room temperature 25°C to 125°C at a rate of 6°C / min for reaction for 3.5 hours, the temperature is continued to be raised to 150°C at a rate of 6°C / min for reaction for 12.5 hours, the temperature is continued to be raised to 175°C at a rate of 6°C / min for reaction for 2 hours, and then cooled to room temperature 25°C with the furnace to obtain a cured titanium-modified phenolic composite material semi-finished product; the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent replacement temperature is maintained at 60°C, the anhydrous ethanol is replaced every 24h, and it is replaced 5 times, and finally vacuum dried at 170°C (the vacuum drying pressure is 10kPa) for 12h to obtain a lightweight ceramicizable titanium-modified phenolic-based composite material.

[0068] The density of the lightweight ceramic titanium-modified phenolic-based composite material prepared in this embodiment is 0.52 g / cm 3 The thermal conductivity along the fiber thickness direction is 0.056W / (m·K), and the heat flux density is 3.6MW / m 2 The surface temperature of the sample exceeded 1900°C and the back surface temperature was only 94°C when it was exposed to the oxyacetylene flame for 30 seconds.

[0069] The lightweight ceramicizable titanium-modified phenolic-based composite materials prepared in Examples 1 to 3 of the present invention can be used at a high heat flux density of 3.6 MW / m 2 The surface temperature of the composite material exceeds 1900°C and the back temperature is only 73°C to 94°C when it is placed in an oxyacetylene flame for 30 seconds. This indicates that the lightweight, ceramicizable titanium-modified phenolic-based composite material prepared in Examples 1 to 3 of the present invention can play a ceramicizing role in the field of short-term high heat flux insulation, and can also play a role in reverse radiation heat dissipation on the surface, and can play a role in efficient insulation in a high heat flux density environment.

[0070] Example 4

[0071] Embodiment 4 is substantially the same as Embodiment 1, except that:

[0072] ③Preparing a titanium-modified phenolic resin solution: adding the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② within 10 seconds, and stirring at a speed of 300 r / min for 30 minutes to obtain a titanium-modified phenolic resin solution; wherein the mass ratio of the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② is 1:1.

[0073] In this example, excessive gelation occurs during the stirring process, and the composite material cannot be impregnated and composited. This indicates that the stirring time plays a key role in the molding and preparation of the lightweight, ceramizable titanium-modified phenolic-based composite material of the present invention.

[0074] Example 5

[0075] Embodiment 5 is substantially the same as Embodiment 1, except that:

[0076] ③Preparing a titanium-modified phenolic resin solution: adding the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② within 10 seconds, and stirring at a speed of 300 r / min for 2 minutes to obtain a titanium-modified phenolic resin solution; wherein the mass ratio of the phenolic solution obtained in step ① to the titanium-containing solution obtained in step ② is 1:1.

[0077] The titanium-modified phenolic-based composite material prepared in this example has a local uneven phenomenon, and the overall density of the composite material is about 0.45 g / cm 3 The thermal conductivity along the fiber thickness direction is 0.054W / (m·K), and the heat flux density is 3.6MW / m 2 The surface temperature of the sample exceeded 1900°C and the back surface temperature was 109°C when it was exposed to the oxyacetylene flame for 30 seconds.

[0078] Comparative Example 1

[0079] ① At 20°C, add 13 g of butyl titanate to 120 g of acetylacetone while stirring, and continue stirring until a uniform mixed solution A1 is formed.

[0080] ② At 20°C, the mixed solution A1 was slowly and uniformly added dropwise to 700g of an ethanol solution of a boron-modified phenolic resin (THC-800 produced by Shaanxi Taihang Fire Retardant Polymer Co., Ltd.) having a rubber content of 60wt% under stirring; the dropping speed was 4.5mL / min; the stirring speed was 200r / min.

[0081] ③ After the dropwise addition is completed, continue stirring at 20°C for half an hour at a stirring speed of 200 r / min to obtain titanium-modified phenolic resin.

[0082] ④Impregnation, curing, solvent replacement and drying: The titanium-modified phenolic resin obtained in step ③ was vacuum impregnated at a pressure of 10 kPa to obtain a volume density of 0.16 g / cm 3The carbon fiber preform is vacuum impregnated at room temperature 25°C and the vacuum impregnation time is 30min; after taking out the impregnated carbon fiber preform, the temperature is raised from room temperature 25°C to 120°C at a rate of 5°C / min for reaction for 3 hours, the temperature is continued to be raised to 155°C at a rate of 5°C / min for reaction for 12 hours, the temperature is continued to be raised to 180°C at a rate of 5°C / min for reaction for 3 hours, and then cooled to room temperature 25°C with the furnace to obtain a cured titanium-modified phenolic composite material semi-finished product; the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent replacement temperature is maintained at 60°C, the anhydrous ethanol is replaced every 24h, and it is replaced 4 times, and finally vacuum dried at 180°C (the vacuum drying pressure is 10kPa) for 12h to obtain a titanium-modified phenolic-based composite material.

[0083] The density of the titanium-modified phenolic-based composite material prepared in this comparative example is 0.63 g / cm 3 , at a heat flux of 3.6MW / m 2 The surface temperature of the sample exceeds 1900℃ and the back surface temperature is 170℃ when it is exposed to the oxyacetylene flame for 30s.

[0084] Comparative Example 2

[0085] Comparative Example 2 A modified high temperature resistant ablation insulation composite material was prepared with reference to Example 1 of Chinese patent application CN 115850906 A.

[0086] The modified high temperature resistant ablation insulation composite material prepared in this comparative example has a heat flux density of 3.6 MW / m 2 The surface temperature of the sample exceeded 1900°C and the back surface temperature was 117°C when it was exposed to the oxyacetylene flame for 30 seconds.

[0087] Comparative Example 3

[0088] Comparative Example 3: Referring to Example 1 of CN 112851383 A, an infrared radiation-resistant, lightweight, ablation-resistant composite material with an added sunscreen was prepared.

[0089] The infrared radiation resistant, lightweight, and ablation resistant composite material with added sunscreen prepared in this comparative example has a heat flux density of 3.6 MW / m 2 The surface temperature of the sample exceeded 1900°C and the back surface temperature was 106°C when it was exposed to the oxyacetylene flame for 30 seconds.

[0090] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a lightweight ceramic titanium-modified phenolic-based composite material, characterized in that: The method comprises the following steps: (1) mixing a phenolic resin and a solvent and stirring at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a phenolic solution; in the phenolic solution, the mass ratio of the phenolic resin to the solvent is (6 to 9):20; (2) mixing the curing agent and the solvent and stirring at room temperature at a speed of 200 to 400 r / min for 1 to 3 hours to obtain a mixed solution, and then adding titanate to the mixed solution and mixing evenly to obtain a titanium-containing solution; in the titanium-containing solution, the mass ratio of the curing agent, the titanate and the solvent is (0.5 to 2): (0.1 to 3): 30; (3) adding the phenolic solution to the titanium-containing solution within 10 seconds, and stirring at a speed of 200 to 400 r / min at room temperature to obtain a titanium-modified phenolic resin solution; in step (3), the mass ratio of the phenolic solution to the titanium-containing solution is 1:(0.8 to 1.2); in step (3), the stirring time decreases with the increase of the titanate content in the titanium-containing solution. When the mass ratio of the titanate to the solvent in the titanium-containing solution is greater than or equal to 0.1:30 and less than 1:30, the stirring time is 20 to 25 minutes. When the mass ratio of the titanate to the solvent in the titanium-containing solution is (1 to 2):30, the stirring time is 8 to 10 minutes. When the mass ratio of the titanate to the solvent in the titanium-containing solution is greater than 2:30 and less than or equal to 3:30, the stirring time is 8 to 10 seconds. (4) The fiber preform is impregnated with a titanium-modified phenolic resin solution, and then cured, solvent replaced and dried in sequence to obtain a lightweight, ceramicizable titanium-modified phenolic-based composite material.

2. The preparation method according to claim 1, characterized in that: In step (1): The phenolic resin is one or more of barium-modified phenolic resin, boron-modified phenolic resin, silicon-modified phenolic resin, zirconium-modified phenolic resin and epoxy-modified phenolic resin.

3. The preparation method according to claim 1, characterized in that: In step (1) and / or step (2), the solvent is one or more of methylformamide, propylene glycol, ethylene glycol, dimethylaniline, and methylpyrrolidone; In step (2), the curing agent is one or more of paraformaldehyde, hexamethylenetetramine, aniline, formaldehyde, and melamine; and / or In step (2), the titanate is one or more of ethyl titanate, isopropyl titanate, and butyl titanate.

4. The preparation method according to claim 1, characterized in that: In step (4): The curing is as follows: first curing at 110-135°C for 2-4 hours, then curing at 140-165°C for 12-14 hours, and then curing at 170-195°C for 2-4 hours; Anhydrous ethanol is used for solvent replacement, the temperature of solvent replacement is 50-70° C., the time of each solvent replacement is 18-30 hours, and the number of solvent replacements is 3-6 times; and / or The drying is vacuum drying at 170-190°C.

5. The preparation method according to claim 4, characterized in that: The vacuum drying pressure is 1-10 kPa.

6. The preparation method according to claim 1, characterized in that: The fiber preform adopts one or more of continuous carbon fiber, quartz fiber, glass fiber and organic fiber; The fiber preform has a structure of a stitching structure, a needle-punched structure, a web structure, a 2.5D braided structure or a three-dimensional braided structure.

7. The preparation method according to claim 6, characterized in that: The fiber preform is a three-dimensional needle-punched structure.

8. The preparation method according to claim 1, characterized in that: The density of the fiber preform is 0.15-0.36 g / cm 3 , thickness is 10-30mm, single wire diameter is 6-7μm, needle density is 15-20 needles / cm 2 .

9. The preparation method according to claim 1, characterized in that: The fiber preform is impregnated with a titanium-modified phenolic resin solution under a pressure of 1 to 10 kPa.

10. A lightweight, ceramizable titanium-modified phenolic-based composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of titanium-modified phenolic resin

    CN109160988B

  • Light anti-infrared radiation ablation-resistant composite material added with opacifying agent and preparation method thereof

    CN112851383A

  • Modified high-temperature-ablation-resistant heat-insulation composite material and preparation method thereof

    CN115850906A

  • Modified boron-phenolic resin and preparation method and application thereof

    CN106117964A

  • Expanded microsphere modified fiber reinforced phenolic aerogel composite material as well as preparation method and application thereof

    CN117430912A